Getting agriculture involved in addressing climate change - Thomas Rosswall, CGIAR - Rosswall, R (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2009)
In this video, agriculture research expert Thomas Rosswall discusses how farmers lie at the heart of a climate solution. Thomas Rosswall is Chairman of the CGIAR Challenge Programme on Climate Change, Agriculture and Food Security (CCAFS). Agriculture generally, and farmers especially, are vital to mitigate and adapt to climate change. More than a billion farmers and their families around the world are on the front line of climate change. Their lives and livelihoods are directly affected by its impact, and they are also vital to implementing many of the solutions we need to help delay and deflect it. Therefore, farmers must be involved in implementing climate change mitigation and adaptation strategies. To support them, we must create sound and reliable incentives; we must share knowledge; and we must make adequate tools and technologies accessible to deliver both food and energy security. Increasing farm productivity in a sustainable way and decreasing waste and losses can significantly mitigate the effects of climate change, prevent deforestation, and protect biodiversity. Adopting proven sustainable agricultural practices reduces greenhouse gas (GHG) emissions and enhances the effect of natural carbon sinks. Further research and innovation are essential to invent the necessary adaptation and mitigation solutions.